PENGAJARAN APRESIASI NILAI-NILAI CERITA RAKYAT âEMPAT RAJAâ DALAM PEMBELAJARAN BAHASA INDONESIA SEBAGAI MODEL PEMBELAJARAN KONTEKSTUAL DI KABUPATEN RAJA AMPAT - Wutoy, Fanda Yunita; Baru, Yosefina (Universitas Papua Manokwari, 2016)
The main focus of the research is to reveal educative values contained in Empat Raja âFour Kingsâ Folklore. It is hoped that this research can serve as an Indonesian language teaching medium with contextual learning model containing local or Papuan literatures, especially folklores from Raja Ampat areas. Contextual learning model is a model in implementing literature appreciation learning which helps the teachers to tie the materials Â and studentsâ real world. The method used in this research was descriptive-qualitative with data collection which were obtained from Empat Raja âFour Kingsâ folklore. The data were collected by usinginterview and observation technic and were analyzed by using value analysis and classification. Moreover, there are four educative values acquired from Empat Raja âFour Kingsâ folklore: (1) educative religious value, (2) educative moral value, (3) educative social value, and (4) educative cultural valueÂ Â